Description of a new Coelorinchus (Macrouridae, Gadiformes, Teleostei) from Taiwan, with notable new records of grenadiers from the South China Sea - Iwamoto, Tomio; Ho, Hsuan-Ching; Shao, Kwang-Tsao (Zootaxa, 2009)
Among recent collections of grenadiers procured from fishery ports in northeastern Taiwan were ten specimens of an undescribed species of Coelorinchus, which we here describe as C. fuscigulus sp. nov. One of the specimens was recorded previously as C. cylindricus Iwamoto and Merrett, 1997, but that species differs from the new species most notably in having a complete bony support of the anterolateral snout margin, compared with margin incompletely supported. Other differences include proportional measurements (preoral length, orbit diameter, distance orbit to preopercle, postorbital length of head, length of upper jaw, and body depth), scale row counts, and body markings. Three other species (Coryphaenoides asper, Coelorinchus spinifer, Kumba gymnorhynchus) recently collected by deepwater trawls in the South China Sea are the second records for the species; specimen data are provided for these species.